The influence of demographic factors on online loan decision - Eko Ganiarto (President University, 2022)
Knowing the factors that influence the decision to use online loan services, especially demographic factors, is very important for online loan service providers. Thus, online loan service providers will be more focused and effective in offering their services to prospective customers. This quantitative study aims to know the influence of demographic factors on online loan decisions. The online loan decision as the dependent variable used in this study was measured by using seven statement indicators. Meanwhile, the demographic factors as independent variables consist of gender, age, education, occupation, and income. Data were obtained from 382 respondents in the Central Java area through online questionnaires, then processed and analyzed using the regression analysis. The results showed that: (1) the influence on using online loans for the female is less than males; (2) The baby boomer generation (oldest age group) has the higher influence on using online loans than other generations; (3) People with SMP/Junior High School education have the higher influence on using online loans compared to other education groups; (4) Housewives have the higher influence on using online loans compared to another occupation group; (5) people who have income between Rp 5,000,000 - Rp 7,499,999 has the higher influence on using online loans compared to other income groups. Thus, online loan service providers must be more selective and focus on marketing their services, using demographic information/data from potential customers, such as male customer, baby boomer generation, housewives, people with SMP education, and People who has income between Rp 5,000,000 – Rp 7,500,000.